(untitled) (Pravaha, 2018)
Work- family balance” is a term that refers to an individual’s perceptions of the degree to which s/he is experiencing positive relationships between work and family roles, where the relationships are viewed as compatible and at equilibrium with each other. Like a fulcrum measuring the daily shifting weights of time and energy allocation between work and family life, the term, “workfamily balance,” provides a metaphor to countervail the historical notion that work and family relationships can often be competing, at odds, and conflicting. There was a time when the boundaries between work and home were fairly clear. Today, however, work is likely to invade our personal life — and maintaining work-life balance is no simple task. Family work balance is a complex issue that involves financial values, gender roles, career path, time management and many other factors. Every person and couple will have their own preferences and needs. The problem of maintaining a balance between work life and family life is not a new one. But in the recent few years social scientists have started paying more attention to it. Now there is growing concern in Nepal and experts are of the view that a constant struggle to balance both sets of life will have serious implications on the health of an employee. The seriousness of this problem increases many times in the cases of women workers in our society which is a traditional one and where women are still supposed to have greater family responsibilities. They are expected to look after their children, entertaining the guest, taking care of their parents, in laws and other elderly members of their families as also managing kitchen and other household affairs. Neglecting any of these responsibilities for the sake of discharging work in office or in other institutions where they are employed is not tolerated by their husbands and other male members of the society. We talk of women empowerment but we fail to understand the problems which working women are facing in the tradition bound society like of ours. The study is a pioneering work to investigate into this problem. It is a modest attempt to understand the manner in which women workers try to maintain balance between their work and family lives. The study also explores the ways and means by which female workers can be enabled to maintain proper balance between the two sets of their lives. The findings of this study may be of great use to employers, and business executives as well, who have now come to realize that the responsibility to maintain a healthy work life balance rests on both the organisation and employee. Pravaha Vol. 24, No. 1, 2018, Page: 217-232